Documents in the Firkovich Collection: Valuable Sources on the History of the Jewish Communities in Europe and the Middle East from the 12th to the 19th century - Vasilyeva, Olga (Karaite Archives, 2014)
The paper presents a survey of the manuscript collections of Avraham Firkovich, and, in particular, of the handwritten documents it contains in Hebrew, Arabic, West-Russian and other languages. These historical documents belonged to the Karaite (mostly of Lithuania), Rabbanite and Samaritan communities, and reflect their life in Europe and the Middle East from the 12th to the 19thcentury. These historical sources were included in different library funds and described in several inventory hand-lists; some archival materials have been presented in printed catalogues, and many items have been published and translated into European languages. In the paper, a brief survey of the documents is given, as well as the history of their acquisition by Firkovich and the history of their cataloguing and research over the past 150 years.